Posthuman Creativities: Democratizing Creative Educational Experience Beyond the Human. Issue 1 (March 2022) - Rousell, David; Harris, Daniel X.; Wise, Kit; MacDonald, Abbey; Vagg, Julia
This chapter explores the urgent relevance of posthumanist theory and practice for democratizing creative educational experiences in 21st-century schools, universities, and informal learning environments. Posthumanism challenges the myopic centering of the human in creative education in an age of climate change, artificial intelligence, and zoonotic disease, where nonhuman agencies are intricately imbricated in human cultures and lives. Using a cartographic methodology, the chapter critically maps key theories and debates in posthumanist creativity studies across four substantive fields of inquiry: (a) process philosophy, (b) affect studies, (c) place-based education, and (d) creative ecology. Drawing links between theoretical concepts and practical examples of creative experience across formal and informal education contexts, the chapter scopes an alternative agenda for critical studies of creativity in light of the posthuman turn.